Fluid flow properties of slotted flat- and hollow-blade impellers - Georgiev, D. (Array, 2008)
Summary: Published data on flow field variation caused by various blade design patterns are scarce. Most designs exhibit significant flow separation and adverse pressure gradients effects that lower mixing efficiency. In view of the design potentials of the CFD methodology, the flow field variations caused by different blade designs could be classified in order to be able to predict the spread of the low pressure regions behind blades while retrofitting existing equipment towards energy-saving performance without decreasing the impeller blending and dispersing capacity related to the geometry considered. The aim of the present study is to reveal such variations for some conventional flat blade modifications. The performance of three flat and hollow blade design modifications comprising slotted and perforated blades are examined. The specific power drawn, pumping capacity, deformation rate and turbulence intensity are determined and compared. The impeller power effectiveness is discussed in terms of the strain deformation rate produced. Evidence for enhanced performance of slotted and perforated designs is presented